Coffin–Lowry syndrome: a systematic review of RPS6KA3 confirmed cases and implications for diagnosis and counseling - Maity, Sabyasachi; Montion, Miranda; Boothe, Danielle; Attarpour, Mona; Mageto, Ivy; Agarwal, Simran; Patel, Rujul; Lark, Chloe; Cardona Valentin, Nemesis; Quinones-Budel, Esther; Shireen, Hafsah; Gadad, Bharathi S.; et al. (Frontiers in Genetics, 2026)
BackgroundCoffin–Lowry syndrome (CLS) is a rare X-linked disorder caused by pathogenic variants in RPS6KA3, presenting with intellectual disability, distinctive facial and skeletal features, and variable systemic involvement. Advances in genomic technologies have expanded the mutation spectrum, yet genotype phenotype correlations remain incompletely understood.MethodsWe conducted a systematic review of published cases (n = 72) following PRISMA guidelines. Demographic, phenotypic, and genotypic data were extracted, standardized, and summarized using descriptive statistics. Associations between mutation type and key clinical features were assessed with Chi-square or Fisher’s exact tests. Diagnostic approaches and global distribution were also analyzed.ResultsThe cohort comprised 50 males (69.4%) and 22 females (30.6%), median age 12 years (range: 1–45). Developmental delay (87.5%) and intellectual disability (66.7%) were the most frequent features, alongside musculoskeletal deformities (kyphoscoliosis 33.3%, pectus anomalies 19.4%) and neurologic involvement (SIDEs 12.5%, seizures 15.3%, spasticity 5.6%). Frameshift variants showed the strongest associations with SIDEs (35%, p = 0.009) and seizures (24%, p = 0.048), while splice-site mutations were linked to spasticity and cardiomyopathy. No consistent clustering of intellectual disability severity by mutation type was observed. Diagnostic methods varied, with most cases confirmed by sequencing approaches (e.g., Sanger, WES, next-generation sequencing panels), supplemented by array-based CNV detection. Geographically, cases were reported across Asia, Europe, and North America, with the largest clusters from China (14), USA (14), and Japan (9).ConclusionThis systematic review highlights recurrent neurodevelopmental, neurologic, and skeletal phenotypes in CLS and delineates mutation-specific risks, particularly for SIDEs and seizures. The findings emphasize the value of comprehensive genomic testing, raise awareness of maternal germline mosaicism, and underscore the utility of reproductive technologies such as PGT-A/M for at-risk families. Beyond clinical and research implications, this work provides an accessible reference for affected families seeking clearer prognostic insights.Systematic Review RegistrationIdentifier CRD420223404871.